Zastosowanie drzew klasyfikacyjnych do identyfikacji rodzaju zmian u pacjentów z pojedynczym cieniem okrągłym płuca - Szlachcińska, Aleksandra; Witaszczyk, Anna; Misztal, Małgorzata (The Use of Classification Trees in the Differential Diagnosis of Lesion in Patients with Solitary Pulmonary Nodules, 2009)
In the paper, the dataset of 50 patients, treated surgically due to the solitary pulmonary nodule on the chest computed tomography was analysed. The study was conducted to identify preoperative features (from the laboratory tests and from the chest computed tomography scans) associated with the type of the lesion (benign or malignant) and to develop some classification rules assigning patients to the selected subgroups before histopatological examination of the lesion. Decision rules were established on the basis of logistic regression model and tree-structured algorithms: CART and LOTUS. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 442-450